2014
DOI: 10.1002/2013jd021096
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium deficiency caused by heterogeneous reactions during a super Asian dust episode

Abstract: Mineral dust particles exert profound impacts on air quality, visibility, and ocean biogeochemistry. Interactions between dust particles and other anthropogenic pollutants modify not only the size spectrum and morphology but also physicochemical properties of dust particles, thereby affecting their radiative properties and ability to act as cloud condensation nuclei and in turn their impact on climate.Here we report field observations on the surface chemical transformations in a super Asian dust plume captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 84 publications
(161 reference statements)
4
17
0
Order By: Relevance
“…In the NWPac region, there was also good agreement between the 73 ship-based observations from 2005 to 2008 in the 25-30 • N, 120-125 • E cell and the 173 daily observations made during 2010 at Pengchiayu Island (25 • 37 44 N, 122 • 4 4 E) in the East China Sea (Hsu et al, 2014). The Pengchiayu dataset indicated that there was some seasonality in aerosol NO − 3 concentrations at this site ( Fig.…”
Section: Comparison To Concentrations At Island Monitoring Stationssupporting
confidence: 61%
See 1 more Smart Citation
“…In the NWPac region, there was also good agreement between the 73 ship-based observations from 2005 to 2008 in the 25-30 • N, 120-125 • E cell and the 173 daily observations made during 2010 at Pengchiayu Island (25 • 37 44 N, 122 • 4 4 E) in the East China Sea (Hsu et al, 2014). The Pengchiayu dataset indicated that there was some seasonality in aerosol NO − 3 concentrations at this site ( Fig.…”
Section: Comparison To Concentrations At Island Monitoring Stationssupporting
confidence: 61%
“…Much of the observational work on dust has generated data on aerosol N concentrations, augmenting the data available in these regions, but the presence of dust adds extra complexity to the comparison performed here. Uptake of nitric acid onto suspended mineral dust particles alters the size distribution and deposition velocity of aerosol nitrate, and changes the gas-phase composition of N (Hanisch and Crowley, 2001;Rubasinghege and Grassian, 2009 (Lamarque et al, 2013b). In general, modelled dust deposition fluxes to remote ocean regions have been shown to vary by factors of 10 or more (Huneeus et al, 2011;Schulz et al, 2012) and to not reproduce key aspects of the dust cycle even in well-characterised regions (Prospero et al, 2010).…”
Section: Role Of Mineral Dust In Modifying N Deposition Fluxesmentioning
confidence: 99%
“…The second half of each PTFE filter was subjected to extraction with 20 mL of Milli-Q water (18.2 Ω) for 1 h, and ionic species concentration were determined through ion chromatography (Dionex ICS-90 for cations and ICS-1500 for anions), which was equipped with a conductivity detector (ASRSeULTRA). The water-soluble ionic species were K + , Na + , Mg 2+ , Ca 2+ , NH 4 + , SO 4 2-, NO 3 -, and Cl -, were analyzed with a precision better than 5% (Hsu et al, 2014). More information can be found in Lin et al (2016).…”
Section: Chemical Components Analysismentioning
confidence: 99%
“…Mineral aerosols contain soluble materials (slightly soluble calcium salts, such as CaCO 3 ). Additionally, heterogeneous reactions between acid gases and minerals lead to significant increases in water‐soluble calcium, magnesium, and aluminum [ Cao et al ., ; Duvall et al ., ; Hsu et al ., ]. The inclusion of water‐soluble minerals could increase the cloud water alkalinity, affecting SO 2 dissolution and the rate of aqueous‐phase oxidation of S(IV), especially for O 3 and NO 2 [ Seinfeld and Pandis , ].…”
Section: Model Descriptionmentioning
confidence: 99%